Efficiency and time resolution of monolithic silicon pixel detectors in SiGe BiCMOS technology. (1st February 2022) - Iacobucci, G.; Paolozzi, L.; Valerio, P.; Moretti, T.; Cadoux, F.; Cardarelli, R.; Cardella, R.; Débieux, S.; Favre, Y.; Ferrere, D.; Gonzalez-Sevilla, S.; Gurimskaya, Y.; et al.
Abstract: A monolithic silicon pixel detector prototype has been produced in the SiGe BiCMOS SG13G2 130 nm node technology by IHP. The ASIC contains a matrix of hexagonal pixels with pitch of approximately 100 μm. Three analog pixels were calibrated in laboratory with radioactive sources and tested in a 180 GeV/c pion beamline at the CERN SPS. A detection efficiency of (99.9-0.2 +0.1 )% was measured together with a time resolution of (36.4 ± 0.8) ps at the highest preamplifier bias current working point of 150 μA and at a sensor bias voltage of 160 V. The ASIC was also characterized at lower bias voltage and preamplifier current.